The Relationship between the Role of Parents and the Level of Independence of Mentally Retarded Children - Rudhiati, Fauziah; Dewi, Eva Aprilia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Mental retardation is a condition with less intelligence. Mentally retarded children are not capable in academic terms, so that mentally retarded children can only be trained to become more independent children. Independence is strongly influenced by the role of parents. Children who often interact with parents will find it easier to make friends and be able to be independent and socialise. Objective: The objective of this study was to determine the relationship between the role of parents and the independence of mentally retarded children. Method: his study used a descriptive correlation study with a cross sectional approach. The sample in this study were 27 respondents in pairs between parents and the child in SLB C Cipaganti. The sampling technique used was purposive sampling. Parental role questionnaires based on aspects of fostering, loving and nurturing were used to collect data on parental roles, while data on the independence of mentally retarded children were collected through observation sheets. Results: Based on the results of univariate analysis, it is known that 48.1% of parental roles are in the less category and 66. 7% per cent of children in the category of not independent. Based on Chi Square, there is a relationship between the role of parents and the independence of mentally retarded children (Pvalue 0.021 < α 0.05) .Conclusions: parents can improve guidance and education for mentally retarded children to form better independence by always guiding and training children in the use of language, socialising and how to care for themselves.